Feedforward Rotor Fault Compensation. Issue 6 (8th February 2020) - Wu, Matheus F.; Cavalca, Katia L.; Markert, Richard
Summary: When damaged, it is not unusual to observe nonlinear responses in previously linear structures. Specifically, in rotating machinery context, unbalance, misalignment, bearing, and shaft damage occur during operation, and their responses arise as a combination of multiple modes and harmonics. These vibration effects are undesirable and, besides compromising the system performance, can propagate or generate further faults. In practice, the machine cannot be simply stopped for repairs, and a method for provisory attenuating such problems is desirable. The fault effects can be approximated by a set of loads distributed along the healthy rotor linear model approximation. Intuitively, one can also estimate counteractive forces to mitigate the fault symptoms. Therefore, this work proposes a simple feedforward approach to detect and compensate fault effects at multiple harmonics in rotors. The compensating force is calculated to minimize the least square modal difference between healthy and faulty rotor. A test rig is operated in distinct conditions to demonstrate and validate the method highlighting different fault symptoms (unbalance, misalignment, and shaft bow).